LncRNA LINC01857 drives pancreatic adenocarcinoma progression via modulating miR-19a-3p/SMOC2 (Clinics, 2022)
Objectives: Emerging evidence has demonstrated that LINC01857 exerts a pivotal function in many cancers. However, its function in Pancreatic Ductal Adenocarcinoma (PDAC) still remains unclear. This study was designed to investigate the regulatory character of LINC01857 in PDAC.Methods: Bioinformatic tools and databases were used to seek potential miRNAs and mRNAs. Gene expression was evaluated by Reverse Transcription quantitative real-time Polymerase Chain Reaction (RT-qPCR), and western blot was used for protein level detection. A subcellular fraction assay was done to ascertain the location of LINC01857 in PANC-1 and BxPC-3 human pancreatic cancer cells. CCK-8, EdU, wound healing and Transwell assays were performed to inquire into the influence of LINC01857, and SPARC -related Modular Calcium-binding protein-2 (SMOC2) on cell viability, proliferation, migration, and invasion, respectively. The interaction between LINC01857 and its downstream genes was explored by RNA immunoprecipitation and luciferase reporter assays.Results: LINC01857 levels were significantly elevated in PDAC. Knockdown of LINC01857 significantly restrained the proliferation, migration, invasion, and Epithelial-Mesenchymal Transition (EMT) process of PDAC cells. MiR-19a-3p was a downstream target of LINC01857, and miR-19a-3p levels were significantly decreased in PDAC cells. In addition, SMOC2 expression had a negative correlation with that of miR-19a-3p, and SMOC2 was a downstream target of miR-19a-3p. Furthermore, SMOC2 upregulation partially abolished the inhibitive influence of LINC01857 downregulation on cell proliferation, migration, invasion, and the EMT process.Conclusion: LINC01857 promotes malignant phenotypes of PDAC cells via upregulation of SMOC2 by interacting with miR-19a-3p.